The effect of micro-osteoperforations on the rate of maxillary incisors' retraction in orthodontic space closure: a randomized controlled clinical trial - Carolina Morsani Mordente; Dauro Douglas Oliveira; Juan Martin Palomo; Polyana Araújo Cardoso; Marina Araújo Leite Assis; Elton Gonçalves Zenóbio; Bernardo Quiroga Souki; Rodrigo Villamarim Soares (SpringerOpen, 2024)
Abstract Background This single-centered randomized controlled clinical trial aimed to evaluate the effectiveness of micro-osteoperforations (MOPs) in accelerating the orthodontic retraction of maxillary incisors. Methods Forty-two patients aged 16-40 were recruited and randomly assigned into two groups, one which underwent MOPs (MOPG) in the buccal and palatal region of all maxillary incisors immediately before the start of retraction and one which did not (CG). Eligibility criteria included the orthodontic need for maxillary first premolars extraction and space closure in two phases. The primary outcome of the study consisted of measuring the rate of space closure and, consequently, the rate of incisors' retraction using digital model superimposition 14 days later and monthly thereafter for the next 4 months. The secondary outcomes included measuring anchorage loss, central incisors' inclination, and root length shortening, analyzed using cone beam computed tomography scans acquired before retraction and 4 months after retraction. Randomization was performed using QuickCalcs software. While clinical blinding was not possible, the image's examinator was blinded. Results Twenty-one patients were randomly assigned to each group. However, due to various reasons, a total of 37 patients (17 male and 20 female) were analyzed (mean age: 24.3 ± 8.1 years in the MOPG; 22.2 ± 4.2 years in the CG) during the trial. No statistically significant difference was found between the MOPG and the CG regarding the incisors' retraction measured at different time points at the incisal border (14 days, 0.4 mm vs. 0.5 mm; 1 month, 0.79 mm vs. 0.77 mm; 2 months, 1.47 mm vs. 1.41 mm; 3 months, 2.09 mm vs. 1.88 mm; 4 months, 2.62 mm vs. 2.29 mm) and at the cervical level (14 days, 0.28 mm vs. 0.30 mm; 1 month, 0.41 mm vs. 0.32 mm; 2 months, 0.89 mm vs. 0.61 mm; 3 months, 1.36 mm vs. 1.10 mm; 4 months, 1.73 mm vs. 1.39 mm). Similarly, no statistically significant differences were detected in the space closure, anchorage loss, central incisors' inclination, and radicular length between groups. No adverse effect was observed during the trial. Conclusions MOPs did not accelerate the retraction of the maxillary incisors, nor were they associated with greater incisor inclination or root resorption. Trial registration ClinicalTrials.gov NCT03089996. Registered 24 March 2017- https://clinicaltrials.gov/ct2/show/NCT03089996 .